2020
DOI: 10.1039/d0fo00620c
|View full text |Cite
|
Sign up to set email alerts
|

“Influence of diet on mood and social cognition: a pilot study”

Abstract: Diet, mood & social cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Yelverton reported that fiber, magnesium, niacin, thiamine, and folate were positively related to pregnancy [49]. Ugartmendia reported taking less soluble fiber as a factor of frailty for young male and female patients [50]. To our knowledge, this is the first report of WHO-5 and nutrients in older people; however, it is likely that WHO-5 score was improved by the supplementation of nutrients that were initially deficient.…”
Section: Discussionmentioning
confidence: 76%
“…Yelverton reported that fiber, magnesium, niacin, thiamine, and folate were positively related to pregnancy [49]. Ugartmendia reported taking less soluble fiber as a factor of frailty for young male and female patients [50]. To our knowledge, this is the first report of WHO-5 and nutrients in older people; however, it is likely that WHO-5 score was improved by the supplementation of nutrients that were initially deficient.…”
Section: Discussionmentioning
confidence: 76%
“…Here we focused on specific dietary components. Fat, carbohydrates, and fruit and vegetable intake had been identified in the literature to play a key role in mood and wellbeing ( 13 , 14 , 65 ). Our findings supported the role of fruit and vegetable intake in concurrent wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent Spanish study [72] also observed the negative impact on mental health of diets that defer from the traditional Mediterranean Diet, and the association between mental health aspects and macronutrients. The authors concluded that a healthy diet, rich in complex carbohydrates, insoluble fibre, and aspartate, and low in cholesterol could be beneficial for mental health [72].…”
Section: Austin Publishing Groupmentioning
confidence: 96%